VD_FINDINFO Décision / 2025 / 306 vom 29. April 2025 - VD Tribunal cantonal (2025)
PRINCIPE DE LA CÉLÉRITÉ, PROPORTIONNALITÉ, RISQUE DE RÉCIDIVE, OPPORTUNITÉ | 29 al. 1 Cst., 36 al. 3 Cst., 197 al. 1 let. c CPP (CH), 221 al. 1bis CPP (CH), 237 CPP (CH), 383 al. 1 CPP (CH), 5 al. 1 CPP (CH)